Factors related to depression in adults with oral health problems in Spain (2017 to 2020) - Cebrino, Jesús; Portero de la Cruz, Silvia (Frontiers in Public Health, 2024)
Background: The need to study the link between gender, depression, and oral health is becoming increasingly evident. This study therefore aimed to determine the prevalence and evolution over time of depression among women and men with oral health problems and to evaluate the association between depression status, lifestyle-related variables health-related variables and use of dental health services in those people. Methods: We performed a nationwide cross-sectional study on 25631 adults with oral health problems residing in Spain from the Spanish National Health Survey 2017 and the European Health Survey of Spain 2020, including as the main variable self-reported diagnosis of depression. We analysed independent variables such as lifestyle-related variables, health-related variables, and variables related to dental health services. Sociodemographic characteristics were considered as control variables. Results: The prevalence of depression among adults with oral health problems in Spain was 7.81% (10.14% for women, 5.39% for men), with a notable decrease from 2017 to 2020 in women. Depressed women had a slightly higher percentage of filled or capped teeth, and had more covers (crowns), bridges or other types of prostheses or dentures, while men had more caries. Women also made more frequent, regular dental visits for check-ups and mouth cleaning, whereas men often needed extractions. Unfavourable associated factors in both genders were: perceiving their health as good, average, poor, or very poor, and having 1–2 and ≥ 3 comorbidities. Conversely, not being a current smoker was related to less likelihood of depression. In women only, not engaging in leisure-time physical activity produced more unfavourable associated factors. Conclusion: The prevalence of depression among adults with oral health problems in Spain from 2017-2020 was 7.81%, but this figure has been steadily decreasing over time. In addition, the favourable and unfavourable associated factors could help us inform health professionals and authorities in order to prevent depression and enhance the care of this population according to gender.